2010
DOI: 10.4269/ajtmh.2010.09-0339
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, Knowledge, and Practices Regarding Malaria Prevention and Treatment among Pregnant Women in Eastern India

Abstract: Abstract. We explored views toward and use of malaria prevention and treatment measures among pregnant women in Jharkhand, India. We conducted 32 in-depth interviews and six focus group discussions (total = 73 respondents) with pregnant women in urban, semi-urban, and rural locations in a region with moderate intensity malaria transmission. Most respondents ranked malaria as an important health issue affecting pregnant women, had partially correct understanding of malaria transmission and prevention, and repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
52
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 14 publications
12
52
2
1
Order By: Relevance
“…Actually, only one variable (being single) had a statistically significant association with having knowledge on malaria prevention and control. While the level of CHWs' knowledge and attitudes on malaria prevention and control seems high in this study, it falls within the range of good knowledge and attitudes (50-99%) recorded in similar studies conducted in Colombia [20], India [21], Ethiopia [22], Iran [23], Tanzania [24], Ghana [25], Nigeria [26] and Cameroon [27]. The highest level of knowledge (99%) on malaria transmission, prevention and control so far has been reported in a study done in Cameroon [27].…”
Section: Discussionsupporting
confidence: 67%
“…Actually, only one variable (being single) had a statistically significant association with having knowledge on malaria prevention and control. While the level of CHWs' knowledge and attitudes on malaria prevention and control seems high in this study, it falls within the range of good knowledge and attitudes (50-99%) recorded in similar studies conducted in Colombia [20], India [21], Ethiopia [22], Iran [23], Tanzania [24], Ghana [25], Nigeria [26] and Cameroon [27]. The highest level of knowledge (99%) on malaria transmission, prevention and control so far has been reported in a study done in Cameroon [27].…”
Section: Discussionsupporting
confidence: 67%
“…Other sources of malaria treatment such as clinics and drug shops were also mentioned by pregnant women. This act of self-treatment is consistent with findings from study done in other part of Uganda [28] and other studies done in India [29], Tanzania [22], and Bangladesh [25]. A few of the pregnant women reported not to have got treatment for malaria.…”
Section: Discussionsupporting
confidence: 90%
“…This is similar to the 2010 Indian research that indicated that the respondents had partially correct understanding of malaria transmission, treatment and prevention. [7] Major aspects of the knowledge, perceptions and practice of malaria management that the students seem to have done poorly include species of Plasmodium that cause malaria infection in human, the most common species that cause malaria infection, the most commonly used laboratory technique to detect malaria parasite, information about malaria prophylaxis, most effective antimalarial drugs currently used, among others, as substantial number of students have some knowledge gap in these areas. These were largely responsible from the final fair knowledge outcome.…”
Section: Discussionmentioning
confidence: 99%
“…[6] The findings from a study on the attitude, knowledge and practices regarding malaria prevention and treatment showed that the respondents had partially correct understanding of malaria transmission, treatment and prevention. [7] The outcome of another research work on the knowledge and practices on malaria treatment measures in Abeokuta, Nigeria revealed 65% of the participants had three to four episodes of malaria per year while 27% of respondents stated general body pain and headaches as symptoms associated with malaria. [8] Another research on knowledge, attitude and management practices on malaria in Anambra State, Nigeria, stated that 40.1% of respondents visited hospital for malaria treatment, 57% of respondents said malaria is caused by malaria parasite, 50.9% used ACTs in malaria treatment and 27.4% stated fever, chills, vomiting, body ache and headache as symptoms of malaria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation